2011
DOI: 10.1055/s-0031-1296502
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Truncated Area under the Curves in the Bioequivalence Evaluation of Long Half-Life Drugs

Abstract: The bioequivalence of long terminal half-life drugs, donepezil (CAS 120014-06-4) 10 mg and memantine (CAS 19982-08-2) 10 mg, was evaluated by comparing the results obtained for the total areas under the concentration time curves (AUC(0-inf)) with those for partial AUCs: AUC(0-216h), AUC(0-72h) and AUC(0-48h). Pharmacokinetic endpoints were determined by standard formulas from the concentration-time courses of the parent compounds donepezil and memantine. The results of the bioequivalence assessment based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In addition, the pharmacodynamic half-life of drugs that change receptor activation levels is much longer than the tens of seconds the network activity is sustained. For instance the half-life of donepezil is well over 48 hr [38]. Therefore as a first approximation, the neuromodulatory effect is averaged over the full time range of the simulation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the pharmacodynamic half-life of drugs that change receptor activation levels is much longer than the tens of seconds the network activity is sustained. For instance the half-life of donepezil is well over 48 hr [38]. Therefore as a first approximation, the neuromodulatory effect is averaged over the full time range of the simulation.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have demonstrated bioequivalence with truncation at 24 and/or 48 hr using studies similar to those used here . Marzo et al .…”
Section: Discussionmentioning
confidence: 56%
“…A crossover design was planned as per the USFDA requirements. For comparative bioavailability studies, this is considered as the preferred design in order to minimize subject-by-subject variations and to minimize variability between drug treatments [13]. …”
Section: Discussionmentioning
confidence: 99%